Building the Machine: The Importance of Governance in Obesity Policy - Pengilley, Andrew J.; Kelly, Paul M. (Frontiers in Public Health, 2018)
The Australian Capital Territory (ACT) is a small Australian jurisdiction with a single tier of government and a population of approximately 400,000 people. Despite enjoying comparatively high levels of income, education, physical amenity and access to nutritious food, overweight and obesity is the most prevalent risk factor for chronic disease in the ACT. From 2011, the ACT Government Health Directorate (ACT Health) led the development of a whole of Government plan (the Action Plan) to address obesity. A political imperative to take such action and recent administrative reform assisted the development of a plan with specific actions to be undertaken by different government agencies. Obesity is a ‘wicked problem’ with a diversity of opinion about its causes and potential solutions. These opinions remained influential even when an official course of action had been decided upon. Strong decision making and accountability processes were therefore necessary to support the development of the Action Plan. A lack of understanding beyond the health sector in relation to the evidence for effective, population level interventions to address obesity and a tendency to try and address population health risks by scaling up client-centered models of Government services also proved problematic. This experience highlights the critical importance of designing obesity policy within a robust governance framework in order to ensure progress is made in a highly contested environment. Whilst the observations included here are strongly influenced by local contextual factors, there are important lessons which can be applied elsewhere.